Statistical Assessment of Energy Efficiency of Production and Consumption of Energy Resources in Ukraine - Deina, A. Yu. (Statistics of Ukraine, 2017)
Energy independence of the country - one of the key links of the economy policy of many countries, including Ukraine, which full high-quality functioning of economy depends on. Full functioning of all economic institutes is possible only at reliable providing of fuel and energy resources. Economy life in general fades without skillful and rational use of energy resources. One of the main objectives of sustained economic growth and ensuring energy independence is connected with need of achievement of high, competitive level of efficiency of use of fuel and energy resources. Complex assessment of efficiency of production and consumption of energy resources provides use of a set of the indicators characterizing versatility and complexity of energy efficiency category. The method of multidimensional average has been used for calculation of complex assessment of energy efficiency, at the same time the following indicators have been chosen: energy intensity of GDP, export and import of energy resources, production and consumption of energy resources, investments into the energy complex, oil prices, tariffs for natural gas and the electricity for the population, a share of natural gas in the structure of energy consumption and so on. Complex assessment of efficiency of production and consumption of energy resources is executed on two blocks - for producers and for consumers (population). Extremely low level of energy efficiency for both producers and consumers (population) of energy services during 2010-2016 is observed. At the same time factors which influence the low level of integrated assessment of energy efficiency of production and consumption of energy resources are revealed. Achievements of the actual levels of integrated coefficients of energy efficiency substantially depended recently on introduction of extensive factors of development. Such situation has negative effect on achievement of energy independence of Ukraine. The current state of efficiency of production and consumption of energy resources is characterized by existence of a wide range of problems. It is possible to distinguish the lack of the principles of resource-saving of producers and economical use at consumers of energy services/ It results to very high level of energy consumption, the high level of energy intensity, the need to import of fuel and energy resources from other countries because of insufficiency of own production, the low level of income of consumers and groundlessness of increase in tariffs for energy services that promotes increase in level of debt of the population for the provided services and an unprofitable financial condition of the enterprises of the energy complex.